2015
DOI: 10.1002/ceat.201400797
|View full text |Cite
|
Sign up to set email alerts
|

Slip and Characteristic Velocities in a Horizontal Pulsed‐Plate Extraction Column

Abstract: The slip velocity, the dispersed-phase hold-up, and the characteristic velocities of the phases in a horizontal pulsed extraction column were investigated under no-mass transfer conditions using four binary systems: kerosene-water, toluenewater, n-butyl acetate-water, and butanol-water. The effects of the pulsation intensity, the dispersed-and continuous-phase flow rates, and the interfacial tension on the dispersed-phase hold-up and slip velocity of the phases were investigated. Based on the obtained results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Therefore, it is found that Equations (3)(4)(5) can cover the experimental data accurately in the region from the upper end of the mixer-settler regime to the dispersion regime. On the other hand, they showed poor performance in most of the mixer-settler regime, especially at the lower end of the mixer-settler regime and then became more accurate along the way.…”
Section: Prediction Of the Mean Drop Sizementioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, it is found that Equations (3)(4)(5) can cover the experimental data accurately in the region from the upper end of the mixer-settler regime to the dispersion regime. On the other hand, they showed poor performance in most of the mixer-settler regime, especially at the lower end of the mixer-settler regime and then became more accurate along the way.…”
Section: Prediction Of the Mean Drop Sizementioning
confidence: 95%
“…Also, g is the acceleration due to gravity, a is fractional free area of perforated plates, and the viscosity of the dispersed phase is m d . Moreover, Sreenivasulu et al [17] proposed the following correlation: Figure 8 shows the comparison of some of the experimental data of mean drop size in the vertical section of the column with those calculated by Equation (3) and Equation (4). Accordingly, it is found that available correlations in the literature give a satisfactory prediction of mean drop size in the dispersion regime with an AARE of < 15 %, while the predictive ability of these correlations is poor in the mixer-settler regime with an AARE of > 40 %.…”
Section: Prediction Of the Mean Drop Sizementioning
confidence: 99%
See 3 more Smart Citations